2019
DOI: 10.1128/jvi.00207-19
|View full text |Cite
|
Sign up to set email alerts
|

By Binding CD80 and CD86, the Vaccinia Virus M2 Protein Blocks Their Interactions with both CD28 and CTLA4 and Potentiates CD80 Binding to PD-L1

Abstract: In this article we report that the M2 protein encoded by the vaccinia virus is secreted as a homo-oligomer by infected cells and binds two central costimulation molecules, CD80 (B7-1) and CD86 (B7-2). These interactions block the ligation of the two B7 proteins to both soluble CD28 and soluble cytotoxic T-lymphocyte associated protein 4 (CTLA4) but favor the binding of soluble PD-L1 to soluble CD80. M2L gene orthologues are found in several other poxviruses, and the B7-CD28/CTLA4 blocking activity has been ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
(49 reference statements)
2
18
0
Order By: Relevance
“…Various strains of VACV have been used as vaccines or vectors to treat a number of infections, as well as cancers (44,45). A recent study reported that the M2 protein encoded by the VACV Copenhagen strain can also bind B7 ligands (46), and notably, M2 is absent from certain attenuated VACV strains, for example, modified vaccinia virus Ankara and its derivative Acam3000. Taken together, these findings have implications for the design of poxvirus-based vectors where deletion of the M2 ORF could potentially improve T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Various strains of VACV have been used as vaccines or vectors to treat a number of infections, as well as cancers (44,45). A recent study reported that the M2 protein encoded by the VACV Copenhagen strain can also bind B7 ligands (46), and notably, M2 is absent from certain attenuated VACV strains, for example, modified vaccinia virus Ankara and its derivative Acam3000. Taken together, these findings have implications for the design of poxvirus-based vectors where deletion of the M2 ORF could potentially improve T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells help to confine the antiviral defense and to prevent immunopathology during virus infections (Veiga-Parga et al, 2013). Taken together, viruses can reprogram DC function in antiviral immune responses by tipping the balance between co-inhibitory and co-stimulatory signals as shown for murine cytomegalovirus (Loewendorf et al, 2004; Benedict et al, 2008) and vaccinia virus (Kleinpeter et al, 2019).…”
Section: Function Of Pd-l1 During Acute Virus Infectionsmentioning
confidence: 97%
“…However, CD80 expression increased significantly on DCs co-cultured with oleandrin-pretreated MDA-MB-231 cells. CD80 along with CD86 that are markers of active DCs bind to CD28 on T cells and act as a costimulatory signal for T cell activation 38 . Moreover, oleandrin treatment decreased IL-10 expression but increased IL-2 and IFN-γ secretion.…”
Section: Discussionmentioning
confidence: 99%